Mathematical Conceptual Understanding Profiles of Junior High School Students in Algebra Based on Visual, Auditory, and Kinesthetic Learning Styles - Rohyal Aini; Lalu Sucipto; Nurhardiani Nurhardiani (REVIEW OF MULTIDISCIPLINARY EDUCATION, CULTURE AND PEDAGOGY, 2026)
Mathematical conceptual understanding is a foundational competency in mathematics education, particularly in algebra at the junior high school level. Many students struggle with algebraic concepts, a difficulty believed to be linked to individual learning modalities. This study aimed to analyze the profiles of mathematical conceptual understanding among seventh-grade students at SMPN 23 Mataram, focusing on algebra content and examining differences across Visual, Auditory, and Kinesthetic (VAK) learning styles. A qualitative descriptive design was employed with 30 seventh-grade students categorized using a validated VAK questionnaire, from which three representative subjects were selected through purposive sampling for in-depth analysis. Data were collected through a Conceptual Understanding Test (CUT) comprising ten essay items aligned with five internationally recognized indicators, encompassing concept identification, classification, representation, application, and relational reasoning followed by individual clinical interviews. Analysis followed Miles and Huberman's interactive model with method triangulation to ensure trustworthiness. The findings revealed three distinct in-depth profiles: visual learners excelled in graphical representation and concept classification but were less precise in numerical computation; auditory learners demonstrated strong verbal concept definition and sequential procedural understanding; and kinesthetic learners showed better comprehension through manipulative activities than through abstract presentation. These results confirm that VAK learning styles significantly shape students' mathematical conceptual understanding profiles, offering meaningful insights for qualitatively oriented educational research. Mathematics teachers should therefore integrate differentiated, multi-sensory instructional approaches to address diverse learning needs comprehensively.